2008
DOI: 10.1137/070681053
|View full text |Cite
|
Sign up to set email alerts
|

Necessary and Sufficient Optimality Conditions for Relaxed and Strict Control Problems

Abstract: We consider a stochastic control problem where the set of strict (classical) controls is not necessarily convex, and the system is governed by a nonlinear backward stochastic differential equation. By introducing a new approach, we establish necessary as well as sufficient conditions of optimality for two models. The first concerns the relaxed controls, who are measure-valued processes. The second is a particular case of the first and relates to strict control problems.The criteria to be minimized, over the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…The general case, where the control domain is not convex and the diffusion coefficient depends explicitly on the variable control, was solved by Peng [25] by introducing two adjoint processes and a variational inequality of second order. In a recent work, Bahlali [2] improves and generalizes all the previous results on the subject by introducing a new approach and derive necessary and sufficient optimality conditions in the general case, by using only the first order expansion and the associated adjoint equation.…”
Section: Introductionmentioning
confidence: 96%
“…The general case, where the control domain is not convex and the diffusion coefficient depends explicitly on the variable control, was solved by Peng [25] by introducing two adjoint processes and a variational inequality of second order. In a recent work, Bahlali [2] improves and generalizes all the previous results on the subject by introducing a new approach and derive necessary and sufficient optimality conditions in the general case, by using only the first order expansion and the associated adjoint equation.…”
Section: Introductionmentioning
confidence: 96%
“…In finite dimensional spaces, see [3][4][5][6][7][8][9][10][11][12][13][14], etc. For the cases of infinite dimensional spaces, to our knowledge, in general cases, there are very few papers to treat this problem.…”
Section: Introductionmentioning
confidence: 99%
“…Let us point out that a different relaxation has been used in Bahlali (2008); Ahmed and Charalambous (2013), where the drift and diffusion coefficient have been replaced by their relaxed counterparts. Their relaxed state process is linear in the control variable and is different from ours, in the sense that in our case we relax the infinitesimal generator instead of relaxing directly the state process.…”
mentioning
confidence: 99%
“…Let A = {a 1 , a 2 , ..., a n }, then every relaxed control dtq t (da) will be a convex combination of the Dirac measures dtq t (da) = n i=1 α i (t)dtδ ai (da) , where for each i, α i (t) is a real-valued process such that 0 ≤ α i (t) ≤ 1 and n i=1 α i (t) = 1. It is shown that the solution of the (relaxed) martingale problem (5) is the law of the solution of the following SDE (see Bahlali, 2008) …”
mentioning
confidence: 99%
See 1 more Smart Citation